Preseason and in-season high-speed running demands of 2 professional Australian Rules Football teams - Freeman, B. W.; Talpey, S. W.; James, L. P.; Rayner, R. J.; Young, W. B. (Sports Health: A Multidisciplinary Approach, 2025)
Background: Australian Rules Football athletes complete long preseasons, yet injuries occur frequently at early stages of the competitive season. Little is known about the high-speed running (HSR) prescription during a preseason or whether players are adequately prepared for competition. This study described absolute and relative preseason and in-season HSR demands of 2 professional Australian football teams.